2016
DOI: 10.1001/jamapsychiatry.2015.3278
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Cannabis Use on Human Behavior, Including Cognition, Motivation, and Psychosis: A Review

Abstract: I t is well established that cannabis use causes acute impairment in the ability of the brain to hold information (ie, cognitive capacity). Hence, temporary deficits occur in learning and memory, attention, and working memory.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
500
2
22

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 685 publications
(537 citation statements)
references
References 77 publications
13
500
2
22
Order By: Relevance
“…Over time more and more studies have demonstrated the risk that cannabis use of youths can pose to their developing brains, although causality is difficult to determine because of the possibility of common causal agents [2,17,18]. The results call for additional efforts in intervention specifically aimed at young heavy users of cannabis.…”
Section: Discussionmentioning
confidence: 99%
“…Over time more and more studies have demonstrated the risk that cannabis use of youths can pose to their developing brains, although causality is difficult to determine because of the possibility of common causal agents [2,17,18]. The results call for additional efforts in intervention specifically aimed at young heavy users of cannabis.…”
Section: Discussionmentioning
confidence: 99%
“…However, despite these mixed associations with aggression, adolescent users are at higher risk for current marijuana use to develop into a cannabis use disorder than adult users are (Chen, Storr, & Anthony, 2009;Volkow et al, 2014). Adolescent users might also be at higher risk than adult users for relatively impaired cognitive ability and development of chronic psychosis, and amotivation associated with marijuana use may impact school performance (Lubman, Cheetham, & Yücel, 2015;Meier et al, 2012;Volkow et al, 2016). Fortunately, psychotherapy can effectively counter problematic marijuana use in adolescents (Copeland & Swift, 2009).…”
Section: Adolescents' Personal Use Of Marijuanamentioning
confidence: 99%
“…2,3 The effects of child exposure to secondhand cannabis smoke (SCS) may be harmful as well. 4,5 For example, laboratory studies of the chemical composition of mainstream and sidestream smoke from marijuana cigarettes confirm the presence of known carcinogens and other chemicals linked to respiratory disease. 6 Detectable levels of marijuana metabolites have been found in children exposed to SCS, 7,8 and some toxic chemicals found in both SCS and STS have higher concentrations in SCS than in STS.…”
mentioning
confidence: 99%